The Effect Of Cu Based Tio₂ Nanotubes Array For Heavy Metal Removal - Zaki, Syazwani Mohd (2014)
Heavy metals contamination especially lead (Pb) in wastewater has become a major threat to the health of mankind and environment. The conventional techniques that have been used are not capable of fulfill the requirement of Environmental Protection Agency (EPA) on maximum heavy metal concentration in stream. The maximum contaminant level of Pb(II) is 0.005 mg/L. Therefore, photocatalysis technique was explored to remove Pb(II) in this work. To increase the efficiency of Pb(II) removal, highly order TiO₂ nanotubes array was synthesized using anodization method. The Ti foil was anodized in ethylene glycol containing 0.3 g NH₄F and 1 ml of H₂O at 60 V for 1 hour. TiO₂ nanotubes with diameter of 90 nm and length of 13 μm were obtained upon anodization. Continuous efforts have been exerted to further improve the photocatalytic activity by incorporating Cu in TiO₂ nanotubes by using wet impregnation technique. The effect of as-anodized vs. as-annealed substrate, Cu(NO₃)₂ concentration and temperature were investigated in order to incorporate optimum amount of Cu in TiO₂ nanotubes. It was found that 0.8 wt% of Cu that was incorporated using 0.01M Cu(NO₃)₂ demonstrated the best performance in photocatalytic activity which is 40% better than pristine TiO₂ nanotubes. Further studies were carried out to investigate the effect of pH and initial concentration of Pb(II) absorption by 0.01 M Cu-TiO₂ nanotubes in Ultraviolet (UV) and dark environment.